Drivers of Employee Performance in Public-Sector Utilities: The Relative Roles of Self-Efficacy, Communication, and Organizational Commitment - Lina lina (Institut Bisnis dan Ekonomi Indonesia, 2026)
This study examines the impact of self-efficacy and communication on employee performance in a public-sector utility organization in Indonesia, with organizational commitment considered as a mediating variable. Employee performance is crucial in public service organizations due to its direct implications for service quality and operational reliability. Using a quantitative approach, data were collected through structured questionnaires from 199 employees and analyzed using partial least squares structural equation modeling (PLS-SEM). The measurement model demonstrates adequate validity and reliability. The results indicate that self-efficacy (p < 0.001) and communication (p = 0.010) have significant positive effects on employee performance. Both variables also significantly influence organizational commitment (p < 0.001). However, organizational commitment does not significantly affect performance and does not mediate the relationships between self-efficacy, communication, and performance. The model explains 82.5% of the variance in employee performance (R² = 0.825). This study is limited by its focus on a single organization and a cross-sectional design. Future research should incorporate longitudinal approaches and additional organizational variables. Practically, managers should prioritize strengthening employee self-efficacy and communication effectiveness to improve performance outcomes Keywords: Self-Efficacy, Communication, Organizational Commitment, Employee Performance, PLS-SEM